Dendrimer as a Recent Drug Delivery System: An Overview - Naji, Ghada; Fareed, Noor; Al-Zheery, Worood (Journal of Biomedicine and Biochemistry, 2022)
Dendrimers, their production, characterization, and use in drug de- livery are briefly covered in this article. Dendrimers are classically symmetric nanoscale molecules with an inner core and an outer shell that have well defined, homogeneous, and monodisperse structures. Dendrimers have a unique potential for encasing or entrapping bioac- tive substances because of their tree-like structure. As a result, they could win a prestigious statue in the fields of pharmaceutical, med- ical, and nutraceutical sciences. Numerous advantageous biologi- cal characteristics exist in them, including polyvalency, self-assembly, electrostatic interactions, best chemical stability, and minimal cell tox- icity. While problems with solubility, stability, and bioavailability are limiting concerns for their implementation.